2011
DOI: 10.1186/1472-6963-11-132
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry out-of-hours: a focus group study of GPs' experiences in Norwegian casualty clinics

Abstract: BackgroundFor Norwegian general practitioners (GPs), acute treatment of mental illness and substance abuse are among the most commonly experienced emergency situations in out-of-hours primary healthcare. The largest share of acute referrals to emergency psychiatric wards occurs out-of-hours, and out-of-hours services are responsible for a disproportionately high share of compulsory referrals. Concerns exist regarding the quality of mental healthcare provided in the out-of-hours setting. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
1
16
0
5
Order By: Relevance
“…This distress was also noted in a qualitative study of Norwegian primary care physicians who reported frustration with limited mental health resources after-hours. 41 The lack of integration of mental and medical health care both financially and structurally has been implicated as a factor in the poor health outcomes and increased costs of care in complex patients with cooccurring illness. 42,43 For this reason, the Institute of Medicine has recommended increased integration of services as fundamental to improving the quality of care for patients with co-occurring mental and medical illness.…”
Section: Discussionmentioning
confidence: 99%
“…This distress was also noted in a qualitative study of Norwegian primary care physicians who reported frustration with limited mental health resources after-hours. 41 The lack of integration of mental and medical health care both financially and structurally has been implicated as a factor in the poor health outcomes and increased costs of care in complex patients with cooccurring illness. 42,43 For this reason, the Institute of Medicine has recommended increased integration of services as fundamental to improving the quality of care for patients with co-occurring mental and medical illness.…”
Section: Discussionmentioning
confidence: 99%
“…I en studie som prospektivt hentet inn informasjon om legevaktkontakter relatert til rus og psykiske lidelser, ble truende atferd spontant beskrevet i 32 av 853 journalnotat (4 pst.). Noen leger er bekymret for egen sikkerhet, spesielt i møte med pasienter som er så ruspåvirket eller psykisk syke at deres atferd oppleves uforutsigbar (Johansen, Carlsen & Hunskaar, 2011). Internasjonal forskning tyder på at bekymring for egen sikkerhet reduserer legenes villighet til å delta i vakt (Magin, Adams & Ireland, 2005;Magin, Adams & Sibbritt, 2008;Hobbs, 1994).…”
Section: Ambulansetjenesten Og Bruk Av Politiunclassified
“…Noen av pasientene med rusproblemer eller dårlig psykisk helse er krevende å behandle på legevakt, og vanskelige å henvise videre på grunn av få alternativer til døgninnleg-gelse (Johansen, Carlsen & Hunskaar, 2011). I en 25 år gammel norsk studie ble det observert at legevaktleger kom i klem mellom lekfolk og spesialisthelsetjenesten i psykisk helsevern ved problemstillinger relatert til psykisk sykdom (Måseide, 1991).…”
Section: Samhandling Om Innleggelserunclassified
See 2 more Smart Citations